Toisen silmin - Eve & Ossi; Jämsä, Miika (sellisti); Kytö, Petri; Lehto, Kukka; Malmivaara, Mikko; Mäki-Reini, Eveliina; Mäki-Reini, Ossi; Nikku, Tomi; Nurmi, Leea; Valle, Miika; Vepsäläinen, Mikke (OMR Music, 2016)
11 kappaletta.